INTEGRASI TOKO ONLINE MENGGUNAKAN TEKNOLOGI WEBSERVICE - Yunita Pungki; Budi Santosa; Dessyanto Boedi Prasetyo (Telematika, 2011)
Currently there are many online stores to facilitate sellers to promote their products as well as expand the scope of its work. Online store (webstore) or web e-commerce sales transactions emphasizing that can take place in real time from anywhere as long as it is connected to the net and service orientation to customer / community as its focus. Amazon, Ebay, and Commission Junction is an example webstore. As a burgeoning webstore, they provide many products, ranging from electronic goods, clothing, automotive, jewelry, to books. Sometimes a little trouble if the buyer must access their pages one by one. To that made a sales application designed using webservice technology in order to reduce the problem of data integration from multiple sales sites (Amazon, Commission Junction, and Ebay) so prospective buyers can easily compare various products and prices offered in a market segment. This online sales application created using the PHP programming language and MySQL as the database with data collection methods used in this application is the study of literature and methodology for system development using Waterfall. Resulting software could help the process of integrating data from multiple sales sites (Amazon, Commission Junction, and Ebay). The software also handles the process of adding, changing, and deletion of data products that have been stored in the database. This software is used by 2 users ie visitors / buyers and admin.